Engaging youth in agribusiness through private sector extension and advisory services: Lessons from Rwanda and Uganda - Franzel, Steven; Miiro, Richard; Uwitonze, Nicolas; Davis, Kristin E.; Luzobe, Beatrice; Rurangwa, Raphael (Association for International Agricultural and Extension Education, 2021)
Engaging youth in agribusiness is critical for livelihoods in Africa’s rural areas where millions of youth are unemployed and face many barriers to entry into agribusiness, such as limited education and lack of land (IFAD, 2019). There are initiatives where youth are engaging in private, demand-driven extension and advisory services (EAS), overcoming these constraints (Yami et al., 2019). These initiatives involve youth as either private, for-profit EAS providers (such as when private companies hire young extension agents) or as recipients of private or public sector EAS that guide youth toward self-employment (such as when EAS providers train youth in entrepreneurship). For-profit, private EAS is emphasized in this study because of the rapid growth of commercial agriculture, greater public emphasis on private market mechanisms and the sector’s potential for providing EAS on a sustainable basis (AUC, 2015; DLEC, 2019). While not a substitute for public EAS, private EAS often complement them effectively (Zhou and Babu, 2015, DLEC, 2019).